Finite-time control for fuzzy networked systems with state delay and network-induced delay. (2018) - Yao, Hejun
To investigate the finite-time stabilisation control problem for a class of nonlinear networked systems, a T-S fuzzy model is employed to represent the nonlinear controlled plant with state delay and time varying network induced delay. Based on the Lyapunov stability theory and linear matrix inequality (LMI) approach, a finite-time stabilisation sufficient condition is obtained. Then, a state feedback fuzzy controller which can make the network systems finite-time stable (FTS) is designed. Finally, a numerical example is given to demonstrate the application and effectiveness of the proposed method.